1990
DOI: 10.1093/jn/120.9.977
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-Lowering Activity of Various Undigested Fractions of Soybean Protein in Rats

Abstract: The undigested high-molecular-weight fraction (HMF) of soybean protein prepared after exhaustive digestion by microbial proteases significantly decreased serum cholesterol levels to approximately 45% (p less than 0.05) of those observed with the parent protein in rats fed diets containing cholesterol (0.5%) and sodium cholate (0.125%). HMF bound conjugated bile salts in vitro and significantly increased fecal excretion of both neutral and acidic steroids by 65-95% and 80-170% more, respectively (p less than 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
158
0
11

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 254 publications
(179 citation statements)
references
References 23 publications
10
158
0
11
Order By: Relevance
“…After 4 h hydrolysis, the 10 kDa permeate showed 50.7% cholesterol-reducing activity, which is significantly (P<0.05) higher than that of the unhydrolysed crude casein. These results are in agreement with the findings of Sugano et al [19] who showed that the hypocholesterolemic peptides of soybean protein had molecular masses of 1-10 kDa. In that case, the hypocholesterolemic properties of the peptides were attributed to the inhibition of cholesterol absorption and increases in the faecal excretion of steroids (Mine & Shahidi [20]).…”
Section: Tryptic Hydrolysis and The Rp-hplc Profile Of Caseinsupporting
confidence: 93%
“…After 4 h hydrolysis, the 10 kDa permeate showed 50.7% cholesterol-reducing activity, which is significantly (P<0.05) higher than that of the unhydrolysed crude casein. These results are in agreement with the findings of Sugano et al [19] who showed that the hypocholesterolemic peptides of soybean protein had molecular masses of 1-10 kDa. In that case, the hypocholesterolemic properties of the peptides were attributed to the inhibition of cholesterol absorption and increases in the faecal excretion of steroids (Mine & Shahidi [20]).…”
Section: Tryptic Hydrolysis and The Rp-hplc Profile Of Caseinsupporting
confidence: 93%
“…Sugano et al has shown that undigested high-molecular-weight peptides might effectively bind bile acids in the intestine and thereby increase fecal excretion of both neutral and acidic steroids, resulting in induction of the hypocholesterolemic effect. [7][8][9][10] Thus, high-molecular fraction in soybean peptides can modulate cholesterol metabolism through the stimulation of fecal steroid excretion.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The hypocholesterolemic activity of soybean protein as compared with casein is known to be due to suppression of intestinal cholesterol absorption, 5,6) promotion of fecal steroid excretion, [7][8][9][10] increases in the cholesterol removal rate through the LDL receptor, 1,3,4) and so on. 11,12) Soybean protein has also been found to have triglyceride-lowering action.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A dieta contendo a farinha integral de tremoço apresentou a maior redução de colesterol total e colesterol não-HDL, uma possível causa seria justamente a menor digestibilidade dessa proteína presente nessa dieta, provavelmente devido aos outros componentes bioativos presentes no grão integral, como saponinas, fitoesteróis e fibras (MARTINS et al, 2005 SALTER, 1998;FUKUI et al, 2004). Sugano (1990) e Nagaoka et al (1999) relataram que peptídeos hidrofóbicos de alto peso molecular obtidos após hidrólise enzimática de isolado protéico de soja tem um efeito redutor de colesterol semelhante à proteína intacta. Esses peptídeos resistentes às enzimas tripsina e peptidase, conhecidos como fração não digerível, podem ter propriedade similar aquelas da fibra dietética na sua habilidade de se ligar aos ácidos biliares e colesterol, e assim, aumentar a sua excreção fecal.…”
Section: -Digestibilidade Verdadeiraunclassified